Strengthening Indonesian Language In Government Administration In Mekarjaya, Bayongbong - Zainah Asmaniah; Umi Kulsum; Abdul Hasim; Deasy Aditya Damayanti; Nurul Hasan (Fakultas Kewirausahaan Universitas Garut, 2021)
Abstract The use of good and correct Indonesian is one of the ideals of the nation as stated in the law. This is used as an effort to strengthen government administration at the central to regional levels. Efforts to strengthen the Indonesian language in local government administration are the use of good and correct language in correspondence. They do not know the use of official letter language in accordance with linguistic rules. This is evident from the results of the analysis of errors in correspondence made by the Mekarjaya village apparatus in the Bayongbong sub-district, Garut district. The results of the analysis show that there are many errors in the use of letters and editorial errors, including the use of diction, spelling, effective sentences, titi prey, and letterhead. With these problems, training in writing correspondence in good and correct Indonesian was carried out for the Mekarjaya village apparatus, Bayongbong district, Garut district. The results of the training showed an increase in knowledge and practice in making correspondence according to the standard rules for writing official letters. Abstrak Penggunaan bahasa Indonesia yang baik dan benar merupakan salah satu cita-cita bangsa yang tertuang dalam undang-undang. Hal ini dijadikan sebagai upaya peguatan administrasi pemerintahan baik di jenjang pusat hingga daerah. Upaya penguatan bahasa Indonesia dalam administrasi pemerintahan daerah adalah penggunana bahasa yang baik dan benar pada surat menyurat. Mereka kurang mengetahui penggunaan bahasa surat resmi yang sesuai dengan kaidah kebahasaan. Hal ini terbukti dari hasil analisis kesalahan dalam surat menyurat yang dibuat oleh aparatur desa Mekarjaya di kecamatan Bayongbong kabupaten Garut. Hasil analisis menunjukkan banyaknya kesalahan dalam penggunaan bentuk surat dan kesalahan redaksi surat meliputi penggunaan diksi, ejaan, kalimat efektif, titi mangsa, serta kop surat. Dengan adanya permasalahan tersebut, maka dilakukanlah pelatihan penulisan surat menyurat dengan bahasa Indonesia yang baik dan benar kepada aparatur desa Mekarjaya kecamatan Bayongbong kabupaten Garut. Hasil pelatihan menunjukkan adanya peningkatan pengetahuan dan praktik dalam membuat surat menyurat sesuai dengan aturan standar baku penulisan surat resmi.